Digitalisasi Penjualan Cacing Tanah Puri Kabupaten Pati Berbasis Web - Aviv Huda Nurhayat; Tri Listyorini; Endang Supriyati (Yayasan Literasi Sains Indonesia, 2022)
UMKM is are one of the efforts to improve people's living standards. Earthworm cultivation is very suitable to be developed because more and more people need it, whether it is used for fishing, animal feed, etc. However, for now the cultivation of puri earthworms still has drawbacks, namely the market that is reached is still in the Pati Regency area. To develop this business, efforts will be made to build a system that can be reached by many people outside Pati Regency. In supporting the formation of the application, data collection was carried out using the waterfall method. The creation of an e-commerce web for selling puri earthworms is the result of the existing problems. On this website there is information about earthworms and can also be purchased through this website directly. It is hoped that with this application transactions can be carried out easily and reach many areas.